2014
DOI: 10.1016/j.chiabu.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Physical and sexual abuse in orphaned compared to non-orphaned children in sub-Saharan Africa: A systematic review and meta-analysis

Abstract: This systematic review assessed the quantitative literature to determine whether orphans are more likely to experience physical and/or sexual abuse compared to non-orphans in sub-Saharan Africa (SSA). It also evaluated the quality of evidence and identified research gaps. Our search identified 10 studies, all published after 2005, from Zimbabwe, South Africa, Kenya and Uganda. The studies consisted of a total 17,336 participants (51% female and 58% non-orphans). Of those classified as orphans (n = 7,315), 73% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 57 publications
4
12
0
Order By: Relevance
“…In general, orphans in sub-Saharan Africa may be at risk of experiencing a forced first sexual encounter in comparison to their non-orphaned peers [11,21]. Our findings demonstrate that parental/guardian/caregiver supervision may play a role in reducing these risks, and therefore programs aimed at strengthening parenting skills may merit implementation and future research.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In general, orphans in sub-Saharan Africa may be at risk of experiencing a forced first sexual encounter in comparison to their non-orphaned peers [11,21]. Our findings demonstrate that parental/guardian/caregiver supervision may play a role in reducing these risks, and therefore programs aimed at strengthening parenting skills may merit implementation and future research.…”
Section: Discussionmentioning
confidence: 88%
“…Orphan status has been associated with having an earlier sexual debut, multiple partners, and transactional sex [5], and orphans may be at heightened risk of physical and sexual abuse compared to non-orphans [21,22]. However, some studies in western Kenya have found that orphan status was not significantly associated with increased sexual risk-taking behaviours among adolescents [2325].…”
mentioning
confidence: 99%
“…When studies were pooled in a meta-analysis, the authors concluded that orphanhood was not a significant risk factor for sexual violence. However, the authors noted that both because their findings contradict qualitative findings and “because of inconsistent quality of data and reporting, these findings should be interpreted with caution” (p. 304, Nichols et al, 2014). This leaves the relationship between orphanhood and sexual violence equivocal.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, there is a lack of consistency in these findings. A recently published review found eight studies (from Zimbabwe, South Africa and Uganda) that measured sexual abuse among orphans and non-orphans (Nichols et al, 2014). Only one study reported that orphans were more likely to be sexually abused (Nyamukapa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, orphans may be more vulnerable to sexual victimization, which is known to heighten HIV risk via both direct and indirect pathways (i.e., subsequent risky behaviors and coping mechanisms) [68]. An association between orphanhood and sexual victimization has not been definitively established, however, with a recent meta-analysis citing poor methodological quality as one explanation for the ambiguity [9]. Moreover, while the above mechanisms are largely untested, others do not withstand basic critique: while some orphans demonstrate lower socioeconomic status [e.g., 10 11], evidence suggests that higher socioeconomic groups are most vulnerable to HIV in Africa [1216].…”
Section: Introductionmentioning
confidence: 99%